Variational Discretization of Parabolic Control Problems in the Presence of Pointwise State Constraints (Journal of Computational Mathematics, 2018)
We consider a parabolic optimal control problem with pointwise state constraints. The optimization problem is approximated by a discrete control problem based on a discretization of the state equation by linear finite elements in space and a discontinuous Galerkin scheme in time. Error bounds for control and state are obtained both in two and three space dimensions. These bounds follow from uniform estimates for the discretization error of the state under natural regularity requirements.
Keywords: Parabolic optimal control problem; State constraints; Error estimates.